Antibodies to Human Herpesviruses in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome Patients - Blomberg, Jonas; Rizwan, Muhammad; Böhlin-Wiener, Agnes; Elfaitouri, Amal; Julin, Per; Zachrisson, Olof; Rosén, Anders; Gottfries, Carl-Gerhard (Frontiers in Immunology, 2019)
Myalgic encephalomyelitis, also referred to as chronic fatigue syndrome (ME/CFS) is a debilitating disease characterized by myalgia and a sometimes severe limitation of physical activity and cognition. It is exacerbated by physical and mental activity. Its cause is unknown, but frequently starts with an infection. The eliciting infection (commonly infectious mononucleosis or an upper respiratory infection) can be more or less well diagnosed. Among the human herpesviruses (HHV-1-8), HHV-4 (Epstein-Barr virus; EBV), HHV-6 (including HHV-6A and HHV-6B) and HHV-7, have been implicated in the pathogenesis of ME/CFS. It was therefore logical to search for serological evidence of past herpesvirus infection/reactivation in several cohorts of ME/CFS patients (all diagnosed using the Canada criteria). Control samples were from Swedish blood donors. We used whole purified virus, recombinant proteins, and synthetic peptides as antigens in a suspension multiplex immunoassay (SMIA) for immunoglobulin G (IgG). The study on herpesviral peptides based on antigenicity with human sera yielded novel epitope information. Overall, IgG anti-herpes-viral reactivities of ME/CFS patients and controls did not show significant differences. However, the high precision and internally controlled format allowed us to observe minor relative differences between antibody reactivities of some herpesviral antigens in ME/CFS versus controls. ME/CFS samples reacted somewhat differently from controls with whole virus HHV-1 antigens and recombinant EBV EBNA6 and EA antigens. We conclude that ME/CFS samples had similar levels of IgG reactivity as blood donor samples with HHV-1-7 antigens. The subtle serological differences should not be over-interpreted, but they may indicate that the immune system of some ME/CFS patients may interact with the ubiquitous herpesviruses in a way different from that of healthy controls.